If the Sky Falls : Stories - Montemarano, Nicholas, 1970- (Book collections on Project MUSE., 2005)
If the Sky Falls is the debut short-story collection from award-winning fiction writer Nicholas Montemarano. These eleven stories show why Jayne Anne Phillips has called Montemarano "an American stylist capable of redeeming our darkest dreams." Redemption in these intense and sometimes violent stories is found in the lyrical prose, in the act of storytelling itself. A young man tries to rescue his sister from her abusive lover, and in the process must revisit his own family's violent history ("Note to Future Self"); a home healthcare worker pops pills and takes two men with cerebral palsy to a.